"I'm Sorry My Hair is Blocking Your Smile": A Performative Assemblage and Intercultural Dialogue on the Politics of Hair and Place. Issue 4 (November 2019) - Alexander, Bryant Keith; Stephenson-Celadilla, Ayshia Elizabeth; Alhayek, Katty; Twishime, Porntip Israsena; Sutton, Timothy; Ojeda, Carmen Hernández; Moreira, Claudio
This performative essay is an instance of embodied writing, an assemblage by seven individuals responding to a shared moment from different perspectives on the politics of hair. In the process we engage the sociological imagination as we turn private troubles into public issues, or better yet, we collectively show how public issues are our private troubles.